Development of intercultural creativity through art education at Junior High School: Pengembangan kreativitas interkultural melalui pendidikan seni rupa di SMP - Ndun, Brendha Ockwilya Maharani; Jayola, Cabria Shafa; Rahmatinggusti, Isra’ Kusuma; Rasendria, Muhammad Daiva Khresna; Aristawati, Nabilah Tisti (Universitas Negeri Yogyakarta, 2025)
This study examines the development of students' intercultural creativity through visual arts education at SMP Negeri 15 Yogyakarta, a culturally diverse school. Using a qualitative case study and educational ethnography, the research explores the learning experiences of students and teachers in an intercultural setting. Data was collected through participatory observation, interviews with students from different regions and art teachers, and documentation of student artwork. The findings show that the learning model is adaptive and participatory, fostering active student engagement in the creative process. However, the integration of cultural elements in students' artwork is limited due to low motivation and a lack of cultural understanding. The study recommends incorporating intercultural art projects and digital media to enhance cultural awareness and creative involvement._______________________________________________________________________________ Penelitian ini bertujuan mengeksplorasi pengembangan kreativitas interkultural siswa melalui pembelajaran seni rupa di SMP Negeri 15 Yogyakarta yang memiliki keberagaman budaya. Menggunakan pendekatan kualitatif studi kasus dan etnografi pendidikan, penelitian ini menggali pengalaman siswa dan guru dalam konteks interkultural. Teknik pengumpulan data meliputi observasi partisipatif, wawancara dengan siswa luar daerah dan guru seni budaya, serta dokumentasi karya seni siswa. Hasil penelitian menunjukkan model pembelajaran yang adaptif dan partisipatif, memungkinkan siswa aktif dalam proses kreatif. Namun, unsur budaya dalam karya seni siswa masih terbatas karena rendahnya motivasi dan pemahaman budaya asal.